DETERMINASI STRATEGIS TRANSISI ENERGI DAN DAMPAKNYA TERHADAP KINERJA PERUSAHAAN: ANALISIS PADA INDUSTRI KETENAGALISTRIKAN INDONESIA - Rio Afrianda (STMIK Widuri Jakarta, 2026)
This study aims to analyze the influence of regulatory and political pressures on dynamic capabilities and their implications for the performance of energy companies in the context of the energy transition in Indonesia. The global energy transition is pushing energy companies to adjust their business strategies and improve their organizational capabilities in responding to changes in regulations, technology, and sustainability demands. This study uses a quantitative approach with a survey method of managers and heads of strategic units in energy sector companies in Indonesia. Data were collected through questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that regulatory and political pressures have a positive and significant influence on the dynamic capabilities of energy companies. These findings suggest that changes in energy policies, environmental standards, and political dynamics encourage companies to improve their strategic adaptability and organizational innovation. Furthermore, dynamic capabilities have been shown to have a positive and significant influence on company performance. Companies that are able to effectively integrate, build, and reconfigure organizational resources tend to perform better in the face of changes in the energy sector business environment. This study contributes to the development of strategic management and sustainability literature by demonstrating that dynamic capabilities play a crucial role in linking institutional pressures with improved company performance in the energy transition era. Practically, the results of this study provide implications for energy companies to strengthen organizational capabilities, increase innovation in clean energy technology, and integrate sustainability strategies into long-term business planning.